Reducing Stunting in South Lampung Regency through Preventing Early Marriage: A Critical Analysis - Sari, Ratna Kumala; Prasetya, A. Riva; Zanariyah, Sri; Famulia, Ledy; Terina, Tian; Novalia, Novalia; Mirnasari, Tiar; Pahlevi, Reza (Universitas Internasional Batam, 2024)
South Lampung Regency is recognized as one of the 100 priority districts/cities for addressing child stunting, as designated by the Poverty Reduction Acceleration Team. Efforts to prevent and reduce stunting vary across regions, with the South Lampung Regional Government implementing its own strategies. However, the stunting rate in South Lampung Regency has not shown a significant decline to date. This study aims to analyze policies aimed at reducing stunting rates in South Lampung Regency, with a particular focus on the prevention of early marriage. The research is situated within the framework of public legal policy, specifically addressing the reduction of stunting through measures to prevent early marriage in the region. To this end, a policy-oriented approach was adopted. Findings reveal that early marriage is a contributing factor to growth and developmental disorders in children, manifesting as stunting indicated by height or length measurements below standard norms. The correlation between stunting prevalence and the number of marriage dispensations granted in South Lampung Regency underscores this relationship. The South Lampung Regional Government’s efforts to combat stunting are encapsulated in the South Lampung Regent Regulation Number 15 of 2023, which focuses on accelerating stunting reduction. This policy highlights the critical need to address early marriage as a key strategy in mitigating stunting and ensuring healthier developmental outcomes for children in the region.